Markers of aggressive play are similar among the top four divisions of English soccer over 17 seasons - Sapp, R. M.; Spangenburg, E. E.; Hagberg, J. M. (Science and Medicine in Football, 2019)
Purpose: Aggressive play in professional soccer, punished by referees with fouls and cards, carries increased injury risk. We compared fouls and cards in the English Premier League (EPL) with the next three divisions of English soccer over 17 seasons (2000/01-2016/17), to determine whether previously observed differences with other top European leagues are unique to the EPL or are characteristic of English professional soccer overall. Methods: Data from individual matches were obtained through online sources and season averages for each league were compared. Fouls and cards were also compared between home and away teams. Correlations with final league positions were examined. Results: Numbers of fouls and yellow cards per match did not substantially differ between leagues, with average differences of 3-3.8% and 6.1-14.0% (effect sizes (?p2) < 0.01). Away teams consistently committed more fouls and yellow card offences than home teams in each league. Results were similar though less consistent for red cards. Number and rate of cards awarded to the opposition exhibited strongest correlations with final league position across leagues. Conclusions: Our results suggest similar rates of aggressive play among the top English soccer leagues, possibly due to standardized refereeing style. Consequently, contact injuries rates may be higher in English soccer.